Comparative Study: Enhancing Students’ Reading Comprehension Ability through Ing Ngarsa Sung Tuladha and Student Teams Achievement Division (STAD) Learning Models - Pandiangan, Ezra Novianty (LPPM Universitas Advent Indonesia, 2019)
Cooperative learning is considered to be effective to enhance students’ English skills. This study utilizes two learning models under cooperative learning: Ing Ngarsa Sung Tuladha and Student Teams Achievement Division (STAD). This study aims to find out whether there is a significant difference between those two learning models in enhancing students’ reading comprehension ability. The instrument of this study is the reading test which was piloted before distributing it to the actual respondents. The results of this study show that after comparing the two learning models, there is a significant difference in students' reading comprehension ability. Additionally, in this study, the author seeks respondents' response towards both learning models and it is found that the respondents' response falls under really like category; which means, they really like the two learnings models to be utilized in the classroom to enhance their reading comprehension ability. Keywords: Reading Comprehension Ability, Ing Ngarsa Sung Tuladha, STAD, Cooperative Learning models.